Vital activity limitations and social isolation in psychiatric patients - Prib, Glib (Psychosomatic Medicine and General Practice, 2018)
Background: Medical, social, and professional assessment of patients and the development of a rehabilitation program based on that assessment are important issue in mental and behavioral disorders. However, insufficient consideration of the basic principles of medical and social expertise leads to the inadequate according to patient’s planning and implementation into rehabilitation interventions. Aim: to study the essence and understanding of the concept of "limitation of life" and "social isolation" in the practice of mental health care and rehabilitation. Materials and methods: theoretical analysis and synthesis of scientific sources regarding medical and social rehabilitation of the mentally ill, with disabilities and social isolation. Results: The author expounds his view on development of vital activity limitations and social isolation in psychiatric patients; and on different aspects of using this categories in the medical and social assistance and rehabilitation practice. Conclusion: general trend inherent in both foreign and Ukrainian scientific publications was identified, it highlights the need to build medical and social assistance in accordance with definition of disability and social isolation.